A novel species and a new host record of Trichoderma from caves in Yunnan Province, China - Liu, Xiangfu; Tibpromma, Saowaluck; Gautam, Ajay K.; Suwannarach, Nakarin; Elgorban, Abdallah M.; Chukeatirote, Ekachai; Chethana, K. W. Thilini; Karunarathna, Samantha C. (Phytotaxa, 2025)
Caves offer distinct environmental conditions that foster fungal diversity, and to date, over 2,000 fungal species have been recorded in cave ecosystems. During our surveys of cave fungi in Yunnan Province, China, we isolated several intriguing fungal strains. Detailed morphological characteristics and combined multi-locus phylogeny of internal transcribed spacer (ITS), RNA polymerase II subunit 2 (RPB2), and translation elongation factor 1-alpha (TEF1-α) revealed that four new isolates represent a new species (Trichoderma cavernicola) and a new host record (Trichoderma capillare) in Harzianum clade and Longibrachiatum clade of Trichoderma, respectively. The new species is introduced based on molecular differences and morphological distinctions in colony appearance and size of phialides, supporting cells, conidia, and chlamydospores in comparison to the closely related species. Comprehensive descriptions, micrographs, and phylogenetic analysis results are provided. Furthermore, our findings provide new insights into the understanding of cave fungi and broaden the knowledge of fungal diversity in China.